(untitled) (Indian Journal of Animal Production and Management, 2025)
The present investigation was undertaken to study the breeding efficiency by Tomar method (BET). Data of breeding information were collected from the history sheet registers and herd inventory registers of Hariana cattle maintained at Livestock Farm Complex, UP Pandit Deen Dayal Upadhyaya Pashu Chikitsa Vigyan Vishwavidyalaya Evam Go Anusandhan Sansthan (DUVASU), Mathura. Data on productive animals born between 1962 and 2024 were gathered. A total of 742 animal records were collected from the farm. The mean breeding efficiency was 63.9% with standard error and standard deviation of 0.44 and 11.8, respectively. The coefficient of variation estimated for breeding efficiency was 18.52. The overall least-squares mean for breeding efficiency was estimated as 65.1 ± 0.39%. Significant differences were observed between the periods of birth, AFC classes, and parity of cows for BE. The heritability estimate for breeding efficiency was 0.586.